Miss-Taken Identities: The Comedy of Misrecognition in New Woman Short Stories - Margaret D. Stetz (Cahiers Victoriens et Edouardiens)
This essay will illuminate a surprisingly common trope in British New Woman comic short stories from the late-1880s through the end of the nineteenth century—that is, the social misrecognition of women (almost always young women) by men. Often, this misidentification takes a class-based turn, with men of the upper classes assuming that the girls they encounter in socially ambiguous spaces belong to a class lower than their own and are, therefore, undeserving of the usual forms of respectful courtesy, or are even appropriate targets for sexual predation. These same men often display pre-existing prejudices against women who are smart, talented, and independent. In the course of the narratives that follow, the misidentified female protagonists offer comic correction, re-educating not only the erring men, but also the reader beyond the text. Such stories use the structure of a joke to reshape the understanding of both the diegetic masculine figures within the story and the extradiegetic audience and to advance the cause of the “New Woman” in general by representing this controversial social type as clever, wise, competent, appealing, and even funny. The essay focuses on a number of examples of this phenomenon, including stories by Mabel E. Wotton, Beatrice Harraden, Sarah Grand, and Ellen Thorneycroft Fowler.